(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Vaginal discharge is a common complaint among women of reproductive age presenting in out patient department. In Pakistan Bacterial Vaginosis,Vaginal Candidiasis and Trichomoniasis are the commonest causes of vaginal discharge. Objectives: To determine the frequency of Bacterial Vaginosis, Vaginal Candidiasis and Vaginal Trichomoniasis in women complaining of vaginal discharge. Material and Methods: A prospective descriptive study was carried out at Gynae Department of Govt. Muhammad Nawaz Sharif Hospital, Yakki Gate Lahore over a period of six months. A total of 100 women of reproductive age group with the complaints of vaginal discharge were included in the study. After detailed history all the patients were examined by speculum. Colour, amount, consistency , nature and odour of vaginal discharge was examined. The pH of the vaginal discharge was measured with pH paper. Two high vaginal swabs were taken aseptically. One was used for wet mount and other for Amine test. Results: The mean age of the women was 26.2 years. Fifty five percent of the women with vaginal discharge had bacterial vaginosis, 25 % had trichmoniasis and 20% had vaginal candidiasis. Conclusion: Bacterial vaginosis is the most common cause of vaginal discharge in the women of reproductive age group, followed by vaginal trichomoniasis and vaginal candidiasis in our population.